2008
DOI: 10.1539/joh.l6084
|View full text |Cite
|
Sign up to set email alerts
|

An Occupational Health Study of Emergency Physicians in Japan: Health Assessment by Immune Variables (CD4, CD8, CD56, and NK Cell Activity) at the Beginning of Work

Abstract: An Occupational Health Study of E m e r g e n c y P h y s i c i a n s i n J a p a n : H e a l t h Assessment by Immune Variables (CD4, CD8, CD56, and NK cell activity) at the Beginning of Work: Hiroteru OKAMOTO, et al. Department of Preventive Medicine and Public Health, School of Medicine, Kyorin University-This study was conducted to evaluate the occupational health of Japanese physicians in emergency medicine. Subjects participating in this study were eighty-nine physicians working at 12 medical facilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…In addition, 3-shift work has been associated with reduced T-lymphosyte function (66,67). In more recent studies, NK-cell activity was lower among shift compared to daytime workers; among shift workers, activity was also lower during night as compared to day shifts (68,69).…”
Section: Inflammationmentioning
confidence: 96%
“…In addition, 3-shift work has been associated with reduced T-lymphosyte function (66,67). In more recent studies, NK-cell activity was lower among shift compared to daytime workers; among shift workers, activity was also lower during night as compared to day shifts (68,69).…”
Section: Inflammationmentioning
confidence: 96%
“…This investigation demonstrated that occupational stress may increase anxiety, negatively correlated with blood cytotoxic activity. Reduced blood NK activity was observed in Japan in emergency physicians and nurses with increased work load (Morikawa et al 2005;Okamoto et al 2008). On the other hand, blood NK cell cytotoxicity was signiWcantly reduced in unemployed men and women (Cohen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nakano et al 4) reported that lymphocyte proliferation in shift workers was decreased compared with that of fixed-hour daytime workers in a wholesale market and manufacturing company. Okamoto et al 5) also reported that natural killer (NK) cell activity in rotating shift workers was lower than in workers with fixed daytime schedules in a study of medical doctors. However, these studies utilized cross-sectional designs and a direct, causal relationship between shift work and immune function has not been demonstrated.…”
mentioning
confidence: 99%